Mechanical contributions to muscle injury: Implications for athletic injury risk mitigation - Kalkhoven, J.; Watsford, M. L. (SportRxiv Preprints, 2020)
Muscular injury continues to be a significant burden on athletes. Through developing proper understandings of the mechanical contributions to muscle injury, appropriate intervention protocols can be established to reduce injury risk. The strength, stiffness, length, and elastic properties of the musculotendinous unit underpin the resilience of the structure. The capacity of individual muscles and tendons to absorb elastic energy, protect against high forces, resist length changes and tolerate strain encapsulate the capacity of the musculotendinous unit to avoid injury. Further, the contributions of intersarcomere dynamics to muscle injury are of utmost importance. Considering that muscle injury appears to be more strongly related to muscle fiber strain, opposed to stress, athletes should seek strategies that provide them with the capacity to resist excess strain, which is achieved through correct muscle activation timing, heightened strength and superior stiffness regulation capabilities. Further, athletes should strive to increase their capacity to withstand larger amounts of absolute strain, which can be achieved through increasing the length and maximal elongation capabilities of the structures subject to length changes, such as fascicles.